Исследование этапов проектирования энергоэффективных ИК-сушилок - Загорулько, Андрей Николаевич; Загорулько, Алексей Евгеньевич; Киптелая, Людмила Васильевна (НТУ "ХПИ", 2015)
В работе представлены исследования основных этапов проектирования тепловых аппаратов, поскольку существующие ИК-сушилки имеют недостатки в виде большой производительности, длительной тепловой обработки, значительной энерго- и металлоемкостью, а так же не обеспечивают равномерность тепловых потоков на приемных поверхностях. В связи с этим возникает актуальность в детальном исследовании этапов проектирования современных автоматизированных энергоэффективных ИК-сушилок периодического и непрерывного действия для производства высококачественных сушеных полуфабрикатов из растительного плодоягодного сырья.

The paper presents the study of the main stages of the design of thermal devices, because the existing IR dryers have drawbacks in the form of large-capacity, long-term heat treatment, significant energy and metal, and also do not provide uniform heat flux on the receiving surface. In this regard, there is urgency in a detailed study of the stages of designing energy-efficient modern automated infrared dryer’s periodic and continuous action to produce high quality semi-finished products of dried vegetable raw materials Fruit and Berry. These studies allowed us to develop the optimum design of energy efficient infrared dryers, which have the following advantages: a uniform heat flux across the receiving surface with vegetable raw materials (in the trays and between them) due to the geometric shape of IR dryers; the use of secondary (heated) air and shaking for an intensification of the processes of IR drying vegetable Fruit and Berry raw materials; Low energy and metal designs of devices over existing analogues.
Study design stage energy efficient IR dryers
Keywords: растительное плодоягодное сырье; сушеные полуфабрикаты; приемные поверхности; равномерность тепловых потоков; steps; design; development; IR dryer; optimum shape; uniformity